A Deformable and Highly Robust Ethyl Cellulose Transparent Conductor with a Scalable Silver Nanowires Bundle Micromesh. Issue 36 (13th July 2018) - Xiong, Jiaqing; Li, Shaohui; Ye, Yiyang; Wang, Jiangxin; Qian, Kai; Cui, Peng; Gao, Dace; Lin, Meng‐Fang; Chen, Tupei; Lee, Pooi See
Abstract: Huge challenges remain regarding the facile fabrication of neat metallic nanowires mesh for high‐quality transparent conductors (TCs). Here, a scalable metallic nanowires bundle micromesh is achieved readily by a spray‐assisted self‐assembly process, resulting in a conducting mesh with controllable ring size (4–45 µm) that can be easily realized on optional polymer substrates, rendering it transferable to various deformable and transparent substrates. The resultant conductors with the embedded nanowires bundle micromesh deliver superior and customizable optoelectronic performances, and can sustain various mechanical deformations, environmental exposure, and severe washing, exhibiting feasibility for large‐scale manufacturing. The silver nanowires bundle micromesh with explicit conductive paths is embedded into an ethyl cellulose (EC) transparent substrate to achieve superior optoelectronic properties endowed by a low amount of incorporated nanowires, which leads to reduced extinction cross‐section as verified by optical simulation. A representative EC conductor with a low sheet resistance of 25 Ω □ −1, ultrahigh transmittance of 97%, and low haze of 2.6% is attained, with extreme deformability (internal bending radius of 5 µm) and waterproofing properties, opening up new possibilities for low‐cost and scalable TCs to replace indium‐tin oxide (ITO) for future flexible electronics, as demonstrated in a capacitive touch panel in this work. Abstract : A scalable silver nanowires bundle micromesh is readily achieved by spray‐assisted self‐assembly, rendering a conducting mesh with superior and customizable optoelectronic performance, which is transferable to various deformable and transparent substrates. A washable ethyl cellulose conductor embedded with the AgNWs micromesh is attained, demonstrating additional extreme deformability and chemical reliability, which is promising to replace indium‐tin oxide (ITO) for future flexible electronics.